2016
DOI: 10.21548/33-2-1111
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Berry Epicuticular Waxes in Four Georgian Grape Cultivars (Vitis vinifera L.)

Abstract: The epidermis of plant shoot organs is generally covered by epicuticular waxes. The role of this layer is related mainly to the protection of the inner tissues from biotic and abiotic stresses. In this study, attention is focused on the optical properties of the berry epicuticular waxes of the grapevine (Vitis vinifera L.) at fruit ripening. The reflectance of the berry surface was measured before and after chloroform treatments in four Georgian grape cultivars grown in northern Italy. Epicarp optical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…For each sample, 60 berries were considered in the experimental plan, resulting in a total of 3600 analyzed fruits. Twenty berries were selected to represent the control blank and kept in dark conditions at 24 • C. Other 20 berries were exposed to artificial light after epicuticular wax removal (to maximize chlorophyll excitation avoiding light filtration according to Rustioni et al (2012)) for a 4 h period. Two LED lighting systems (version LumiGrowTM Pro 325, LumiGrow, Novato, CA, USA) were used.…”
Section: Experimental Designmentioning
confidence: 99%
“…For each sample, 60 berries were considered in the experimental plan, resulting in a total of 3600 analyzed fruits. Twenty berries were selected to represent the control blank and kept in dark conditions at 24 • C. Other 20 berries were exposed to artificial light after epicuticular wax removal (to maximize chlorophyll excitation avoiding light filtration according to Rustioni et al (2012)) for a 4 h period. Two LED lighting systems (version LumiGrowTM Pro 325, LumiGrow, Novato, CA, USA) were used.…”
Section: Experimental Designmentioning
confidence: 99%
“…3.79) [31]. Rustioni and collaborators investigated the spectral properties of the epicuticular waxes of Vitis vinifera L. grape berries during ripening [32]. This experiment demonstrated that berry waxes have specific reflectance properties which are useful to monitor grape ripeness and maturity at harvest based on their wax content [32].…”
Section: Innovative Applicationsmentioning
confidence: 99%
“…The Folin-Ciocalteu method was used for the determination of the total polyphenols as suggested by L. Rustioni et al, 2014 [14]. In brief, an aliquot (0.5 ml) of the appropriate diluted skin and seed extracts were added to a 10 mL volumetric flask, containing 2.5 ml of distilled water.…”
Section: Analysis Of Total Polyphenolsmentioning
confidence: 99%